Pengaruh Islamic Religiosity dan Teacher Support terhadap Student Engagement Pada Siswa Kelas XI - Ratih Ratih; Tri Na’imah; Ugung Dwi Ario Wibowo; Itsna Nurrahma Mildaeni (CV. ITTC INDONESIA, 2025)
The level of student engagement within the school environment plays a crucial role in supporting effective learning implementation. Effective learning is expected to assist students in achieving educational goals, which include the development of self-awareness, spiritual and religious strength, intelligence, personality and good character, as well as essential life skills for both the individual and society. This study aims to examine the influence of Islamic religiosity and teacher support on student engagement among 11th grade students at MAN 4 Cirebon. This research employed a quantitative approach with a sample of 175 students selected through simple random sampling. Data were collected using the Student Engagement Scale (SES), the Islamic Religiosity Scale, and the Teacher Support Scale for Secondary School (TSSSS). The results of the data analysis showed that Islamic religiosity significantly influences student engagement, teacher support significantly influences student engagement, and both Islamic religiosity and teacher support jointly influence student engagement. The R Square value of 0.411 indicates that Islamic religiosity and teacher support contribute 41.1% to student engagement, while the remaining 58.9% is influenced by other unexamined factors.